Aplikasi Kamus Bahasa Daerah Manggarai Berbasis Android: - Helena Danur; Kristianus Jago Tute; Benediktus Yoseph Bhae (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2022)
Indonesia is an archipelagic country that has various ethnicities and languages. Manggarai language is one of the regional languages ​​in Indonesia and is included in the Austrinesian language family. The speakers are located in Manggarai land, namely West Manggarai Regency, Manggarai Regency and East Manggarai, East Nusa Tenggara Province. The problem in this study is that the Manggarai language learning media currently still uses a dictionary in the form of a book to obtain information. The process of searching dictionary words in the form of books can take quite a long time because the search process is conventional or manual, and it is not practical to carry everywhere. the use of dictionaries becomes more practical and speeds up the search for word meanings, so that the local language of Manggarai can continue to be preserved. The research method used in this study is a qualitative method. The data collection techniques used in this research are observation, literature study, interviews, and documentation, while for the development of the system the method used is the Agile method. Application testing using black box testing. The results of this study are that researchers are able to create an android-based Manggarai regional language dictionary application and also create a Manggarai language dictionary application which is currently used by people who want to learn the Manggarai language.